High recurrence rate of eczema herpeticum in moderate/severe atopic dermatitis: TREATGermany registry analysis - Traidl, Stephan; Heinrich, Luise; Siegels, Doreen; Rösner, Lennart; Haufe, Eva; Harder, Inken; Abraham, Susanne; Ertner, Konstantin; Kleinheinz, Andreas; Schäkel, Knut; Wollenberg, Andreas; Effendy, Isaak; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Background Eczema herpeticum (EH) is a disseminated skin infection caused by herpes simplex virus in atopic dermatitis (AD) patients. The frequency of EH and the clinical features of EH patients have not yet been investigated in a larger cohort. Methods We sought to investigate the TREATgermany cohort, a multicenter, non-interventional clinical registry of moderately to severely affected AD patients in Germany. Baseline characteristics of patients included between December 2017 and April 2021 were compared between patients without, single, and multiple EH. Results Of the 893 patients, 195 (21.8%) had at least one EH. Of the 195 patients with EH, 107 had multiple EH (54.9%), representing 12.0% of the total study population. While there were no differences in demographic characteristics, previous treatment, and disease scores at enrollment (itch, IGA, oSCORAD, EASI), patients with EH had more frequent atopic comorbidities and sensitizations to house dust mite, food, and mold. Discussion TREATgermany registry data suggest a high prevalence and recurrence rate of EH, while there appears to be no specific clinical phenotype, besides an increase in allergies, to identify EH patients in the daily routine.
Gesehen am 09.01.2024